FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2013 - Julmi Astina M; Hardi '; Al Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to look at the effect of leverage, liquidity, profitability, public shares, the age of the company on the completeness of the disclosure of financial statements at companies listed on the Stock Exchange in 2011-2013. This research was conducted using secondary data obtained from the annual report from the www.idx.co.id. eknik sampling in this study using purposive sampling technique. The data used in this research is secondary data drawn from the annual reports of companies that meet the criteria. The data collection technique used is the method of documentation, ie secondary data collection activities such as financial reports (financial report), the annual financial statements (annual report). Data analysis method used is by using multiple linear regression analysis performed using a computer program Statistical Product and Service Solution (SPSS) version 20,0.hasil in this study indicate that leverage, liquidity, public shares, firm age has no effect on completeness of the disclosure of financial statements on the company's profitability while the effect on the completeness of the disclosure of financial statements on the company. The magnitude of the effect of the independent variable on the dependent variable, namely 1.6%. It shows there are still other factors that affect the completeness of the disclosure of financial statements.Keywords : Completeness, Disclosure And Finansial Statement